2014
DOI: 10.1016/j.neuron.2014.10.038
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Preclinical Alzheimer’s Disease: Implications for Prevention Trials

Abstract: As the field begins to test the concept of preclinical neurodegenerative disease, the hypothetical stage of disease when the pathophysiological process has begun in the brain but clinical symptoms are not yet manifest, a number of intriguing questions have already arisen. In particular, in preclinical Alzheimer’s disease (AD), the temporal relationship of amyloid markers to markers of neurodegeneration and their relative utility in the prediction of cognitive decline among clinically normal older individuals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
503
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 602 publications
(525 citation statements)
references
References 166 publications
(221 reference statements)
18
503
0
4
Order By: Relevance
“…The well‐established pathological hallmarks of AD include plaques, consisting mainly of amyloid‐ β (A β ) peptides, and neurofibrillary tangles, consisting of phosphorylated tau (p‐tau) protein 2. Prior to the manifestation of symptoms and clinical diagnosis, the neurodegenerative processes have already progressed to a relatively advanced stage with marked synaptic loss and neuronal damage 3. A recent study by Rajan et al has shown that impairment in cognition starts almost 18 years before AD dementia could be clinically diagnosed 4.…”
Section: Introductionmentioning
confidence: 99%
“…The well‐established pathological hallmarks of AD include plaques, consisting mainly of amyloid‐ β (A β ) peptides, and neurofibrillary tangles, consisting of phosphorylated tau (p‐tau) protein 2. Prior to the manifestation of symptoms and clinical diagnosis, the neurodegenerative processes have already progressed to a relatively advanced stage with marked synaptic loss and neuronal damage 3. A recent study by Rajan et al has shown that impairment in cognition starts almost 18 years before AD dementia could be clinically diagnosed 4.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, aging is key risk factor for AD, and studies have suggested that AD has a long preclinical stage from aging to the emergence of clinical symptoms (Sperling et al 2014). In general, mild cognitive impairment (MCI), especially amnesiac MCI, is accepted as an intermediate state between normal aging and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…In general, mild cognitive impairment (MCI), especially amnesiac MCI, is accepted as an intermediate state between normal aging and dementia. The AD neuropathology is an age-dependent progressive process that perhaps lasts decades before the neuropathological diagnostic criteria can be met; it ultimately leads to synaptic loss and neuronal damage in cortical areas of the brain essential for cognitive functions (Sperling et al 2014;Swerdlow 2007). It has been shown that the accumulation of amyloid-β (Aβ), hyperphosphorylation of tau protein, and circuitspecific changes of synaptic connections, such as changed synaptic proteins, appear contribute to AAMI (Chen et al 2007b;Clinton et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several prevention trials have begun to use biomarkers as outcome measures [33,34,[78][79][80], but predominantly as secondary rather than primary outcome measures because no AD biomarker has yet been validated as a surrogate endpoint [81,82].…”
Section: Endpointsmentioning
confidence: 99%